Eccentric-induced delayed-onset muscle soreness impairs cardiac autonomic activity in adolescent athletes: a pre-experimental study El dolor muscular de aparición tardía inducido por contracción excéntrica afecta negativamente la actividad autonómica cardíaca en adolescentes atletas: un estudio pre-experimental - Mabe-Castro, Matías; Mabe-Castro, Diego; Castillo-Aguilar, Matias; Vera Carrasco, Manuel; Valdés-Badilla, Pablo; Guzman-Muñoz, Eduardo; Cares Barrientos, Sergio Oscar; Mendez, Oscar Niño; Nuñez Espinosa, Cristian Andrés (My University, 2024)
Objective: To investigate the impact of eccentric-induced delayed-onset muscle soreness (DOMS) on cardiac autonomic activity in adolescent athletes. Methods: A pre-experimental one-group pre-test/post-test design was carried out on fifteen competitive adolescent athletes, and the effect of DOMS on cardiac autonomic activity was assessed while controlling for body composition and anxious state/trait factors. An eccentric exercise protocol was applied to the elbow's flexor muscles to induce DOMS. Then, heart rate variability was compared before and two days after DOMS induction under resting and resisted movement conditions of the painful limb, using a t-test for paired samples. The body composition and the State-Trait Anxiety Inventory (STAI) were also measured. Results: The analysis revealed a significant effect of DOMS on autonomic response in time domain measures of root mean square of successive differences (RMSSD) (MD = -5.58, 95%CI[-9.36, -1.8], t(14) = -3.2, p = 0.007) and standard deviation of normal-to-normal intervals (SDNN) (MD = -9.43, 95%CI[-15.47, -3.39], t(13) = -3.4, p = 0.005), as well as on sympathetic nervous system (SNS) autonomic indices (MD = 0.68, 95%CI[0.07, 1.29], t(14) = 2.4, p = 0.031) and Stress index (SI) (MD = 2.72, 95%CI[0.67, 4.77], t(14) = 2.8, p = 0.013) under exercise conditions. Conclusions: DOMS changes cardiac autonomic activity compared to control conditions during mechanically evoked pain but not at rest. This study highlights the importance of considering the presence of DOMS when HRV is used in adolescent athletes for training, clinical, or research purposes.
Keywords: acute pain; autonomic nervous system; mechanical hyperalgesia; muscle damage; sports